THE IMPACT OF LONG CANYON DESIGN AND WATERFRONT BARRIER BUILDINGS ON WIND VELOCITY IN A COASTAL AREA OF SELATPANJANG CITY - Boby Rahman; Asri Dinapradipta; Ima Defiana (Universitas Sebelas Maret Surakarta, 2018)
The increase of waterfront buildings’ height has an effect on wind distribution in the urban canyon. On the other hand, the distribution of wind is needed in providing thermal balance in urban environments, especially in urban waterfront coastal areas. This study aimed at observing and analyzing the effect of building height (H) on waterfront buildings and aspects of the length to width (L/W) ratio related to the length of the canyon design. The observation was focused on the wind speed distribution. The research was an experimental research using ENVI-met V3.1 software for simulation. The results indicated that short canyon (low L/W value) results in lower wind speed changes compared to that of long one (higher L/W value) at all altitude levels. The short canyons provided more stability in wind speed reduction. The 15 meters wide of canyon design contributed to the highest average wind speed. Overall, the existence of a barrier building would result in a negative area of air flow and create a calm area within the distance of ± 50 meters.